Evaluation of bone resorptive potential in the treatment of generalized periodontitis - Fastovets, O. O.; Masheiko, I. V.; Lukash, A. Yu.; Лукаш, Анна Юріївна (My University, 2020)
The aim: Is to study dynamics of resorptive potential of bone tissue by indicators of protease and antiprotease systems in the process of treatment generalized periodontitis in patients with age-related osteoporosis and without osteoporotic changes in the skeleton. Materials and methods: In 102 patients, before the start of treatment of generalized periodontitis and in 2, 4 and 12 weeks, the concentration of pro-resorbing matrix metalloproteinases: stromelysin (MMP-3), collagenase (MMP-8) and gelatinase (MMP-9) were determined in blood plasma and mixed oral fluid. The antiresorbtive potential of bone tissue was evaluated by the concentration of a tissue inhibitor of metalloproteinases (TIMP-1) in plasma. The general antiprotease activity was determined by the activity of α1-antitrypsin (α1-AT) and α2-macroglobulin (α2-MG). Results: The most significant changes are recorded for the content of MMP-9 in blood and oral fluid, regardless of the presence of systemic disorders of bone metabolism (P < 0.05). Concentration of MMP-8 is significantly increased in blood plasma and oral fluid in accordance with the severity of the disease and in the course of treatment (P <0.05). The observed increase in the ratio of MMP-8 to TIMP-1 and MMP-9 to TIMP-1 in patients with generalized periodontitis, complicated by systemic osteoporosis (P < 0.05), indicates an imbalance of the protease-antiprotease system. Conclusions: The resorptive potential of bone tissue in patients with generalized periodontitis allows us to correctly choose treatment tactics and to prevent the development of complications.
Keywords: periodontal diseases; osteopenia; matrix metalloproteinases